729 Daily stress and nightmares are bidirectionally associated among nurses. (3rd May 2021) - Garcia, Odalis; Slavish, Danica; Dietch, Jessica; Messman, Brett; Contractor, Ateka; Haynes, Patricia; Pruiksma, Kristi; Kelly, Kimberly; Ruggero, Camilo; Taylor, Daniel
Abstract: Introduction: Nurses may experience frequent nightmares due to stressful work environments. Some studies estimate that 35% of nurses experience nightmares related to experiences at work. Nightmares may also exacerbate stress among nurses, although this has yet to be tested empirically. We examined daily bidirectional associations between stress severity and nightmare occurrence and severity, and whether posttraumatic stress disorder (PTSD) symptoms moderated those relationships. Methods: 392 nurses (mean age = 39.54 years; SD = 11.15; 92% female; 78% White) were recruited for a larger study on sleep and vaccine response. For 14 days, upon awakening, nurses completed daily sleep diaries to assess previous-day stress severity (0 = not at all, 4 = extremely), as well as nightmare occurrence (0 = no nightmare, 1 = nightmare occurred) and nightmare severity (0 = not at all, 3 = very). PTSD symptoms were assessed at baseline using the PTSD Checklist of DSM-5 (PCL-5). Multilevel models were used to examine bidirectional, within-person associations between daily stress and nightmares, and cross-level moderation by baseline PTSD symptoms. Results: Approximately 10.5% of nurses met criteria for PTSD based on PCL-5 scores. 47.2% of nurses reported at least one nightmare across the two weeks. Days with greater stress severity were associated with higher odds of experiencing a nightmare (OR = 1.22, p = 0.001), as well as greater nightmare severity that night (b = 0.09, p = 0.033). Nightmare occurrence (b = 0.15, p < 0.001) was associated with greater next-day stress severity. PTSD symptoms did not moderate daily stress and nightmare associations. Conclusion: Nurses face intense occupational demands and frequent exposure to potentially traumatic events. Our results indicated nightmares and stress may occur in a bidirectional fashion among nurses. Results were similar regardless of nurses' PTSD status. Future studies should explore whether targeting nightmares and stress may improve nurses' health and well-being. Given the essential role that nurses play in maintaining patient health and safety, it is critical to understand the causes and consequences of their sleep-related disturbances. Support (if any):